Novel fluorescent anti-loosening marking material and preparation method thereof

Through the formulation and preparation method of the new fluorescent labeling materials, the corrosion aging problems of existing fluorescent paints in the external environment and the difficulty of identifying bolts looseness are solved, and high luminous intensity, excellent weather resistance and impact resistance are achieved. It is suitable for anti-loose marking in scenarios such as EMU bogies.

CN119799141AActive Publication Date: 2025-04-11METALS & CHEM RES INST CHINA ACAD OF RAILWAY SCI +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510023350.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

Existing fluorescent paints are prone to corrosion and aging when exposed to external environment for a long time, and are difficult to meet the needs of high luminous intensity, multiple luminous bands and excellent comprehensive performance. Especially in scenarios such as EMU bogies, it is difficult to effectively identify the component peeling problems caused by loose bolts.

Method used

A new type of fluorescent labeling material is adopted, and its formulation includes phosphor, ethylene glycol, aqueous polyurethane dispersion, acrylic resin, pure acrylic emulsion and polyethylene glycol. Rare earth phosphors are synthesized by hydrothermal method, and the composite polyurethane resin and acrylic resin are combined to improve the weather resistance and color retention of the paint.

Benefits of technology

It achieves a high and stable fluorescence intensity, enhances the wear resistance, flexibility, weather resistance and impact strength of the paint, and is suitable for anti-loose markings and indicator markings, especially in scenarios such as EMU bogies, which improves the recognition of fasteners.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005232029190000061
    Figure BDA0005232029190000061
  • Figure BDA0005232029190000071
    Figure BDA0005232029190000071
Patent Text Reader

Abstract

The invention provides a novel fluorescence labeling material composition and a fluorescent coating prepared from the same. The novel fluorescence labeling material composition is prepared from the following components in parts by weight: 4 to 14 parts of fluorescent powder, 18 to 35 parts of ethylene glycol, 30 to 50 parts of waterborne polyurethane dispersion, 10 to 21 parts of acrylic resin, 5 to 15 parts of pure acrylic emulsion, 8 to 15 parts of polyethylene glycol and 65 to 160 parts of water. Wherein the fluorescent powder is prepared from the following raw materials: Sr (NO3) 2, Al (NO3) 3, urea, Ce (NO3) 3, Tb (NO3) 3 and Eu (NO3) 3 according to a molar ratio of (100 to 150): (200 to 300): (900 to 1000): (1 to 10): (1 to 90): (1 to 10). The fluorescent paint has the advantages of high luminous intensity, wear resistance, flexibility, weather resistance, strong adhesive force and impact resistance, and is especially suitable for being applied to anti-loosening marks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of coatings, and in particular relates to a novel fluorescent anti-loosening marking material and a preparation method and application thereof. Background Art

[0002] Fluorescent coatings have both coating and fluorescence properties and have been widely used in traffic signs, road markings, safety signs, auto parts, decoration, etc. At present, new fluorescent coatings are not only required to have high luminous intensity, but also require more luminous bands and better comprehensive performance.

[0003] A large number of bolts and other fasteners are used in the bogies and equipment compartments under the EMU. During the running of the train, the bolts will loosen under the action of long-term vibration and aerodynamic load, which may easily cause the bolts to fall off, and then cause the entire component to peel off from the car body. On the one hand, the peeled parts may hit the car body and cause damage. On the other hand, the fallen equipment may fall on the rails, causing unpredictable safety accidents. In order to avoid the problem of component falling off caused by loose bolts, train bolts and other fasteners are generally painted with anti-loosening marks to accurately identify the loosening of bolts. Anti-loosening marks are commonly used for marking bolts, nuts, fasteners and equipment parts. Through the marks, it can be visually detected whether nuts, bolts, fasteners and assembly parts are loose. If the parts are loose, the marks will be obviously broken and deformed, which prompts the maintenance personnel to focus on the inspection and maintenance of the bolts. Since the automatic train was put into operation, many parts have fallen off throughout the railway. At present, on-site staff are in urgent need of high-recognition and long-lasting anti-loosening marks, especially the anti-loosening marking system that is easy to check by the TEDS system.

[0004] Rare earth luminescent coatings have the characteristics of controllable morphology and size, good biocompatibility, high fluorescence color purity, and good physical and chemical stability, which have attracted the interest and research of people in many fields. For example, the Chinese invention patent application with publication number CN110982406A (publication date April 10, 2020) discloses a bismuth oxide (Bi 2 O 3 ) and europium oxide (Eu 2 O 3 ) A composite rare earth luminescent complex, and a low-temperature and crack-resistant water-based fluorescent coating comprising the rare earth luminescent complex.

[0005] The chemical composition, morphology, size and spatial structure of rare earth luminescent materials have an important and decisive influence on their physical and chemical properties. Therefore, designing and synthesizing special rare earth luminescent coatings according to needs is of great significance for improving their performance and exploring their potential applications. Studies have found that lanthanide complexes can enhance the luminescence intensity of rare earth ions due to their unique luminescence properties, but lanthanide elements are difficult to purify and are costly. Exploring high-performance, low-cost rare earth complexes is one of the hot research directions for the development of fluorescent coatings.

[0006] Fluorescent paints are often applied to tunnels, building exterior walls, billboards, etc., and are exposed to the outside for a long time and eroded by rain, snow, wind and frost. Polyester resin is mostly used as the matrix in fluorescent paints, which is easy to hydrolyze in a humid environment and easily react with acidic media. Therefore, outdoor fluorescent paints often suffer from corrosion, aging, and shedding. In order to improve the water resistance and other properties of fluorescent paints, a variety of polymer coating compounding schemes have appeared in the prior art. For example, the Chinese invention patent application with publication number CN116622284A (publication date August 22, 2023) discloses a colorful paint that uses a compound of polyurethane acrylate, epoxy acrylate and polyester acrylate as the main raw materials of the paint, which can be boiled in water at 80°C×1h without falling off.

[0007] As the application scenarios of fluorescent coatings continue to expand, the demand for fluorescent coatings with simple preparation methods, environmental friendliness, low cost, corrosion resistance, and high luminous efficiency is far from being met. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a new type of fluorescent marking material and a preparation method thereof. The fluorescent marking material of the present invention has a reasonable formula, high stability, and high and stable fluorescence intensity, and can be applied to multiple fields such as anti-counterfeiting marks, traffic signs, elastic materials, chemical detection, fluorescent inks, etc. When applied to EMU bogies, undercarriage equipment compartments, etc., it can improve the recognition of EMU anti-loosening marks.

[0009] To this end, the present invention adopts the following technical solution:

[0010] A novel fluorescent marking material composition comprises the following raw materials in parts by weight:

[0011] 4-14 parts of fluorescent powder, 18-35 parts of ethylene glycol, 30-50 parts of waterborne polyurethane dispersion, 10-21 parts of acrylic resin, 5-15 parts of pure acrylic emulsion, 8-15 parts of polyethylene glycol, and 65-160 parts of water.

[0012] Preferably: the novel fluorescent marking material composition comprises the following raw materials in parts by weight:

[0013] 5-12 parts of phosphor, 20-30 parts of ethylene glycol, 35-49 parts of waterborne polyurethane dispersion, 15-21 parts of acrylic resin, 5-10 parts of pure acrylic emulsion, 10-15 parts of polyethylene glycol, 70-150 parts of water.

[0014] Preferably, the raw material composition of the phosphor includes Sr(NO 3 ) 2 、Al(NO 3 ) 3 , urea, Ce(NO 3 ) 3 、Tb(NO 3 ) 3 and Eu(NO 3 ) 3 , the molar ratio is:

[0015] Sr(NO 3 ) 2 ∶Al(NO 3 ) 3 ∶Urea∶Ce(NO 3 ) 3 ∶Tb(NO 3 ) 3 ∶Eu(NO 3 ) 3 =

[0016] (100-150):(200-300):(900-1000):(1-10):(1-90):(1-10);

[0017] A more preferred molar ratio is:

[0018] Sr(NO 3 ) 2 ∶Al(NO 3 ) 3 ∶Urea∶Ce(NO 3 ) 3 ∶Tb(NO 3 ) 3 ∶Eu(NO 3 ) 3 =

[0019] 100:200:1000:1:(10-30):7.

[0020] Preferably, the phosphor is prepared by the following method:

[0021] Sr(NO 3 ) 2 、Al(NO 3 ) 3 Based on the total weight of Sr(NO3 ) 2 、Al(NO 3 ) 3 and urea were dissolved in a 9-12 times by weight anhydrous ethanol-water mixed solution, stirred, and Ce(NO 3 ) 3 、Eu(NO 3 ) 3 and Tb(NO 3 ) 3 , stirring, transferring the obtained white suspension into a reaction kettle, reacting at 200-250°C for 20-24h, cooling naturally after the reaction, filtering, washing the filter cake with water and anhydrous ethanol alternately for 1-3 times, and drying to obtain a phosphor;

[0022] Wherein, in the anhydrous ethanol-water mixed solution, the volume ratio of anhydrous ethanol to water is (2-3):1.

[0023] Preferably, in the anhydrous ethanol-water mixed solution, the volume ratio of anhydrous ethanol to distilled water is 3:1.

[0024] Preferably, Sr(NO 3 ) 2 、Al(NO 3 ) 3 Based on the total weight of Sr(NO 3 ) 2 、Al(NO 3 ) 3 and urea are dissolved in 10 times by weight of the anhydrous ethanol-water mixed solution.

[0025] Preferably, in the preparation of the above phosphor, the drying parameters are 40-60° C., 2-4 h.

[0026] Preferably, the particle size of the aqueous polyurethane dispersion is 0.01-1 μm; more preferably 0.1-0.8 μm.

[0027] The aqueous polyurethane dispersion may be anionic, cationic or nonionic.

[0028] Preferably, the weight average molecular weight of the acrylic resin is 65,000-90,000.

[0029] As a preferred embodiment, in the novel fluorescent marking material composition provided by the present invention, the weight ratio of the aqueous polyurethane dispersion, acrylic resin and pure acrylic emulsion is (6-7):(3-4):1; more preferably 7:3:1.

[0030] Preferably, the polyethylene glycol is selected from one of polyethylene glycol 2000, polyethylene glycol 4000 and polyethylene glycol 6000.

[0031] More preferably, the polyethylene glycol is polyethylene glycol 4000.

[0032] Another object of the present invention is to provide a method for preparing a fluorescent coating, using the novel fluorescent marking material composition as a raw material, comprising the following steps:

[0033] (1) Prepare each raw material component according to weight;

[0034] (2) In a container equipped with a stirring device, the phosphor and ethylene glycol are mixed and stirred evenly; then, an aqueous polyurethane dispersion and an acrylic resin are added, stirred, and the temperature is raised to 50-70° C., and the reaction is kept at this temperature for 2-3 hours to obtain an emulsifier precursor;

[0035] (3) adding polyethylene glycol to the emulsifier precursor obtained in step (2), reacting at 50-70° C. for 2-3 hours to obtain an emulsion emulsifier;

[0036] (4) The emulsion emulsifier obtained in step (3) is naturally cooled to room temperature, pure acrylic emulsion and water are added, stirred for 10-20 minutes, and then dispersed at high speed for 1-2 hours to obtain the fluorescent paint.

[0037] Preferably, in step (4), the rotation speed of high-speed dispersion is 100-200 r / min.

[0038] Another object of the present invention is to provide a fluorescent coating prepared by the above method.

[0039] In addition, the present invention also provides application of the fluorescent paint in anti-loosening marks and / or indication marks.

[0040] The application of the anti-loosening mark refers to applying the fluorescent paint on the surface of the fastener. Once the nut is loose, the fluorescent mark will be deformed, thereby prompting that the fastener is loose.

[0041] The invention adopts a hydrothermal method to synthesize rare earth fluorescent powder, which is characterized by liquid phase reaction. Under high temperature and high pressure conditions, by controlling the amount of rare earth added, special metastable fluorescent powder that can emit different colors is obtained.

[0042] The present invention compounds pure acrylic emulsion with polyurethane resin and acrylic resin in proportion, which can overcome the shortcomings of acrylic resin, improve the physical properties of polyurethane resin, and further enhance the weather resistance, aging resistance and color and light retention of the coating. The structure of the aqueous polyurethane dispersion (polyurethane resin without emulsifier) ​​has urethane chain segments, and has excellent wear resistance and toughness after film formation. Acrylic resin has high light transmittance, strong oil resistance, good oxidation resistance, good weather resistance, and strong adhesion on both polar and non-polar surfaces. However, acrylic resin has the disadvantages of high film forming temperature, low film hardness, poor anti-rebound and poor water resistance, which limits its wide application. The inventor found that compounding acrylic resin with pure acrylic emulsion and aqueous polyurethane dispersion in proportion can overcome the shortcomings of acrylic resin, improve the physical properties (pencil hardness, impact strength, flexibility and solvent resistance) of polyurethane resin, and further enhance the weather resistance, toughness and wear resistance of the coating. In addition, the price of waterborne polyurethane dispersion is relatively high. Compounding it with acrylic resin and pure acrylic emulsion can reduce the amount of waterborne polyurethane dispersion, saving costs while improving the performance of the fluorescent coating of the present invention. However, the amount of acrylic resin and pure acrylic emulsion must be strictly controlled; if the amount of acrylic resin and pure acrylic emulsion added is too much, the comprehensive performance of the coating will decrease.

[0043] Polyethylene glycol is used as a crosslinking agent for polyurethane resin. With appropriate crosslinking strength, a fluorescent coating with excellent mechanical strength, elasticity, wear resistance and oil resistance can be obtained. Polyethylene glycol 4000 has a moderate molecular weight and is a preferred crosslinking agent of the present invention. The inventors found that the toughness and compressive strength of the fluorescent coating can be improved by controlling the addition amount of polyethylene glycol 4000. The possible reasons are: on the one hand, polyethylene glycol 4000 can be used as a toughening agent and emulsifier stabilizer for polyurethane resin and acrylic resin. When the coating is subjected to external impact, it consumes external energy, so that the cracks of the material itself do not easily expand and cause fracture, thereby playing a toughening effect; on the other hand, polyethylene glycol 4000 can give the system a suitable viscosity, form a stable pore structure, and the bubble wall is thick, which can play a buffering role when subjected to external pressure, thereby making the coating excellent in compressive strength. However, if the addition amount of polyethylene glycol 4000 is too much, it will lead to excessive crosslinking, which will reduce the performance of the prepared fluorescent coating.

[0044] In this specification, unless otherwise specified, the "water" refers to purified distilled water, deionized water, etc.

[0045] In this specification, the weight parts of raw materials refer to the mass ratio between the raw materials, rather than the actual mass number. According to the actual situation, 1 weight part can be any mass number, such as 1g, 2g, 5g, 10g, 50g, 500g, 1kg, etc.; it can even not be an integer mass number, such as 1 weight part can be 5.1g, 10.5g, 30.2g, etc. DETAILED DESCRIPTION

[0046] The present invention is described below with reference to specific examples. It will be appreciated by those skilled in the art that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention in any way.

[0047] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.

[0048] Waterborne polyurethane dispersion: HYDRAN from DIC Group;

[0049] Acrylic resin: VONCOAT acrylic acid from DIC Group;

[0050] Pure acrylic emulsion: S-05 pure acrylic emulsion from Shengda New Materials;

[0051] Polyethylene glycol 8000 and polyethylene glycol 4000, Sinopharm Chemical Testing Co., Ltd.

[0052] Example 1 A fluorescent paint

[0053] (1) 5.0 g of phosphor and 20.0 g of ethylene glycol were mixed and stirred, and 35.0 g of aqueous polyurethane dispersion and 15.0 g of acrylic resin were added, stirred at 70° C., and kept warm for 2 h to obtain an emulsifier precursor;

[0054] (2) adding 10.0 g of polyethylene glycol 4000 to the emulsifier precursor obtained in step (1), and reacting at 70° C. for 2 h to obtain an emulsion emulsifier;

[0055] (3) The emulsion emulsifier obtained in step (2) was cooled to 50° C., 5.0 g of pure acrylic emulsion and 70.0 g of deionized water were added, and high-speed dispersion was performed at a speed of 150 r / min for 1 h to obtain a fluorescent coating.

[0056] The preparation method of the phosphor used in step (1) is as follows:

[0057] 0.1 mol Sr(NO 3 ) 2 、0.2mol Al(NO 3 ) 3 and 1 mol urea were dissolved in 1100 g of anhydrous ethanol-deionized water mixed solution (anhydrous ethanol: distilled water = 2.5:1 (v / v)), stirred, and 1 mmol Ce(NO 3 ) 3 、10mmol Tb(NO 3 ) 3and 7mmol Eu(NO 3 ) 3 , stir, transfer the obtained white suspension to a stainless steel reactor lined with polytetrafluoroethylene, seal, and react at 250℃ for 24 hours. After the reaction is completed, cool naturally, filter, collect the filter cake, wash the filter cake alternately with deionized water and anhydrous ethanol for 3 times each, and dry at 50℃ for 3 hours to obtain the phosphor.

[0058] Example 2 A fluorescent material

[0059] (1) 12.0 g of phosphor and 30.0 g of ethylene glycol were mixed and stirred, 48.0 g of aqueous polyurethane dispersion and 15.0 g of acrylic resin were added, stirred at 60° C., and kept warm for 2 h to obtain an emulsifier precursor;

[0060] (2) adding 15.0 g of polyethylene glycol 4000 to the emulsifier precursor obtained in step (1), and reacting at 60° C. for 2 h to obtain an emulsion emulsifier;

[0061] (3) The emulsion emulsifier obtained in step (2) was cooled to 50° C., 8 g of pure acrylic emulsion and 150.0 g of deionized water were added, and high-speed dispersion was performed at a speed of 100 r / min for 1 h to obtain a fluorescent coating.

[0062] The preparation process parameters and method of the phosphor in this embodiment are basically the same as those of the phosphor in Example 1. The difference is that during the preparation of the phosphor, Tb(NO 3 ) 3 The amount added was 20 mmol.

[0063] Example 3 A fluorescent material

[0064] (1) 10.0 g of phosphor and 25.0 g of ethylene glycol were mixed and stirred, 49.0 g of aqueous polyurethane dispersion and 21.0 g of acrylic resin were added, stirred at 70° C., and kept warm for 2 h to obtain an emulsifier precursor;

[0065] (2) adding 10.0 g of polyethylene glycol 4000 to the emulsifier precursor obtained in step (1), and reacting for 2 h to obtain an emulsion emulsifier;

[0066] (3) The emulsion emulsifier obtained in step (2) was cooled to 50° C., 8.0 g of pure acrylic emulsion and 120.0 g of deionized water were added, and the mixture was dispersed at a high speed of 100 r / min for 1 h to obtain a fluorescent coating.

[0067] The preparation process parameters and method of the phosphor in this embodiment are basically the same as those of the phosphor in Example 1. The difference is that during the preparation of the phosphor, Tb(NO 3 )3 The amount added was 30 mmol.

[0068] Example 4 A fluorescent material

[0069] The preparation process parameters and process of the fluorescent coating in this embodiment are basically the same as those in Example 1, except that the polyethylene glycol used is polyethylene glycol 8000, and Tb(NO 3 ) 3 The amount added was 50 mmol.

[0070] Example 5 A fluorescent material

[0071] The preparation process parameters and process of the fluorescent coating in this embodiment are basically the same as those in Example 1, except that during the preparation of the fluorescent powder, Eu(NO 3 ) 3 The amount added was 1 mmol.

[0072] Example 6 A fluorescent material

[0073] (1) 6.0 g of phosphor and 25.0 g of ethylene glycol were mixed and stirred, and 36.0 g of aqueous polyurethane dispersion and 28.0 g of acrylic resin were added, stirred at 70° C., and kept warm for 2 h to obtain an emulsifier precursor;

[0074] (2) adding 10.0 g of polyethylene glycol 4000 to the emulsifier precursor obtained in step (1), and reacting for 2 h to obtain an emulsion emulsifier;

[0075] (3) The emulsion emulsifier obtained in step (2) was cooled to 50° C., 7.0 g of pure acrylic emulsion and 80.0 g of deionized water were added, and high-speed dispersion was performed at 200 r / min for 1 h to obtain a fluorescent coating.

[0076] The preparation process parameters and method of the phosphor used in step (1) are the same as those of the phosphor in Example 1.

[0077] Example 7 A fluorescent material

[0078] The preparation process parameters and process of the fluorescent coating in this embodiment are basically the same as those in Embodiment 1, except that in the preparation process of the fluorescent powder, the volume ratio of ethanol to deionized water in the anhydrous ethanol-deionized water mixed solution is 5:1.

[0079] Example 8 A fluorescent material

[0080] The preparation process parameters and process of the fluorescent coating in this embodiment are basically the same as those in Example 1, except that the polyethylene glycol used is polyethylene glycol 2000, and Tb(NO 3 ) 3 The amount added was 50 mmol.

[0081] Example 9 A fluorescent material

[0082] The preparation process parameters and process of the fluorescent coating in this embodiment are basically the same as those in Example 1, except that the polyethylene glycol used is polyethylene glycol 6000, and Tb(NO 3 ) 3 The amount added was 50 mmol.

[0083] Test Case

[0084] According to the coating industry standard GB / T22374-2018, the fluorescent coating prepared in the above embodiment was tested, and the performance test results are shown in Table 1.

[0085] Table 1 Fluorescent coating performance test results

[0086]

[0087]

[0088] From the results in Table 1, it can be seen that the fluorescent coatings prepared in Examples 1-3 are rich in color, have strong fluorescent luminescence intensity, and have good wear resistance, flexibility, weather resistance, adhesion and impact strength.

[0089] The molecular weight of the polyethylene glycol used in Example 4 is 8000, which causes excessive cross-linking of the polyurethane resin and the acrylic resin, resulting in poor flexibility, adhesion and impact strength of the fluorescent coating.

[0090] In Example 5, Eu(NO 3 ) 3 The doping amount of Eu 3+ With Tb 3+ The doping ratio between them changes, resulting in a weaker fluorescence intensity of the prepared fluorescent coating.

[0091] The mass ratio of the aqueous polyurethane dispersion and the acrylic resin added during the preparation of the fluorescent coating in Example 6 is 9:7. The amount of acrylic resin added is too much. Due to its shortcomings such as high film-forming temperature, low film hardness, poor anti-rebound property, poor water resistance, and poor adhesion, the fluorescent coating has poor wear resistance, flexibility, adhesion, and impact strength.

[0092] In the ethanol-deionized water mixed solution used in the preparation process of the phosphor in Example 7, the ethanol content is relatively high, which causes the reactants to be unevenly dispersed in the ethanol, resulting in low luminous intensity of the phosphor, and further resulting in weak fluorescence intensity of the prepared fluorescent coating.

[0093] The fluorescent coatings prepared in Examples 8 and 9 have better performance than Examples 4-7, but their impact strength is slightly inferior to that of Examples 1-3.

[0094] In summary, the present invention provides a new type of fluorescent coating. Through the compounding of various components, the fluorescent coating of the present invention has high luminous intensity, wear resistance, flexibility, weather resistance, strong adhesion, and impact resistance. In addition to being used as a fluorescent marking coating, it is also particularly suitable as a fastener, especially a fastener anti-loosening fluorescent coating involved in rail transit facilities.

Claims

1. A novel fluorescent marking material composition, comprising the following raw materials in parts by weight: 4-14 parts of phosphor, 18-35 parts of ethylene glycol, 30-50 parts of waterborne polyurethane dispersion, 10-21 parts of acrylic resin, 5-15 parts of pure acrylic emulsion, 8-15 parts of polyethylene glycol, 65-160 parts of water; in, The raw materials of the phosphor include Sr(NO3)2, Al(NO3)3, urea, Ce(NO3)3, Tb(NO3)3 and Eu(NO3)3, and the molar ratio is: Sr(NO3)2:Al(NO3)3:Urea:Ce(NO3)3:Tb(NO3)3:Eu(NO3)3= (100-150)∶(200-300)∶(900-1000)∶(1-10)∶(1-90)∶(1-10)。 2. The novel fluorescent labeling material composition according to claim 1, characterized in that: The raw materials of the phosphor powder include Sr(NO3)2, Al(NO3)3, urea, Ce(NO3)3, Tb(NO3)3 and Eu(NO3)3, and the molar ratio is: Sr(NO3)2:Al(NO3)3:Urea:Ce(NO3)3:Tb(NO3)3:Eu(NO3)3= 100:200:1000:1:(10-30):7。 3. The novel fluorescent labeling material composition according to claim 1 or 2, characterized in that: The phosphor is prepared by the following method: Based on the total weight of Sr(NO3)2, Al(NO3)3 and urea, Sr(NO3)2, Al(NO3)3 and urea are dissolved in 9-12 times the weight of anhydrous ethanol-water mixed solution, stirred, Ce(NO3)3, Eu(NO3)3 and Tb(NO3)3 are added, stirred, the obtained white suspension is transferred to a reaction kettle, reacted at 200-250°C for 20-24h, cooled naturally after the reaction is completed, filtered, the filter cake is washed alternately with water and anhydrous ethanol for 1-3 times, and dried to obtain a phosphor; Wherein, in the anhydrous ethanol-water mixed solution, the volume ratio of anhydrous ethanol to water is (2-3):1; preferably 3:1; Preferably, based on the total weight of Sr(NO3)2, Al(NO3)3 and urea, Sr(NO3)2, Al(NO3)3 and urea are dissolved in 10 times the weight of the anhydrous ethanol-water mixed solution; Preferably, in the preparation of the phosphor, the drying parameters are 40-60° C., 2-4 h.

4. The novel fluorescent labeling material composition according to any one of claims 1 to 3, characterized in that: According to weight parts, it includes the following raw materials: 5-12 parts of phosphor, 20-30 parts of ethylene glycol, 35-49 parts of waterborne polyurethane dispersion, 15-21 parts of acrylic resin, 5-10 parts of pure acrylic emulsion, 10-15 parts of polyethylene glycol, 70-150 parts of water.

5. The novel fluorescent labeling material composition according to any one of claims 1 to 4, characterized in that: The particle size of the aqueous polyurethane dispersion is 0.01-1 μm; more preferably 0.1-0.8 μm; The aqueous polyurethane dispersion is selected from anionic, cationic or nonionic; Preferably, the weight average molecular weight of the acrylic resin is 65,000-90,000.

6. The novel fluorescent labeling material composition according to any one of claims 1 to 5, characterized in that: The weight ratio of the aqueous polyurethane dispersion, acrylic resin and pure acrylic emulsion is (6-7):(3-4):1; more preferably 7:3:

1.

7. The novel fluorescent labeling material composition according to any one of claims 1 to 5, characterized in that: The polyethylene glycol is selected from one of polyethylene glycol 2000, polyethylene glycol 4000 and polyethylene glycol 6000; Preferably, the polyethylene glycol is polyethylene glycol 4000.

8. A method for preparing a fluorescent coating, using the novel fluorescent marking material composition as described in any one of claims 1 to 7 as a raw material, comprising the following steps: (1) Prepare each raw material component according to weight; (2) In a container equipped with a stirring device, the phosphor and ethylene glycol are mixed and stirred evenly; then, an aqueous polyurethane dispersion and an acrylic resin are added, stirred, and the temperature is raised to 50-70° C., and the reaction is kept at this temperature for 2-3 hours to obtain an emulsifier precursor; (3) adding polyethylene glycol to the emulsifier precursor obtained in step (2), reacting at 50-70° C. for 2-3 hours to obtain an emulsion emulsifier; (4) The emulsion emulsifier obtained in step (3) is naturally cooled to room temperature, pure acrylic emulsion and water are added, stirred for 10-20 minutes, and then dispersed at high speed for 1-2 hours to obtain the fluorescent coating; Preferably, in step (4), the rotation speed of high-speed dispersion is 100-200 r / min.

9. A fluorescent coating prepared by the method according to claim 8.

10. Use of the fluorescent paint according to claim 9 in anti-loosening marks and / or indicator marks.

Citation Information

Patent Citations

  • Colored water-based single-component polyurethane waterproof coating and preparation method thereof

    CN115322668A

  • Paints for marking underground facilities and manufacturing method thereof

    KR101398095B1

  • Security element

    US20100295287A1